Arquitetura Como Arte Performativa - tempo, espaço, corpo - Inês Gonçalves da Costa (2022)
From the present reflection on the existence and influence of Architecture in society emerges the importance and dependence that this art represents for the human being; not only on a physical level, as a shelter of our body, but also on an emotional level, as the surroundings of our consciousness. Architecture is the stage of our experiences, it is the structure that surrounds us and motivates both sensations and activities, having an impact on the way human beings relate to each other and to the world. Architecture, as an art made for man, reflects a concern with the relationship it establishes with his body and mind. This one is conceived so that he can discover it, walk through it, live it. The action of man is what gives meaning to this art. His active participation and the involvement of his being, in this immersive experience, is what makes it different from other visual arts, leading to the questioning of its meaning and a search for a semantic framework. This quest motivated the present study, which promotes a critical thinking about the definition of Architecture based on a careful analysis of its function and characteristics.